ETHNOMATHEMATICS AND THE CURRICULUM OF TOMORROW: A FRAMEWORK FOR INCLUSIVE AND PROGRESSIVE EDUCATION - Kumar, Anil; Gopinath, Seema (Ethnomathematics Journal, 2025)
Ethnomathematics, the study of the relationship between culture and mathematical practices, has gained prominence as an approach to fostering inclusivity in education. This research paper explores how ethnomathematics can be integrated into modern curricula to create a framework for inclusive and progressive education. It reviews existing literature, presents a theoretical foundation, details methodologies for studying ethnomathematical practices, and discusses case studies demonstrating successful implementation. The paper further develops a framework for curriculum integration, considers challenges and strategies for implementation, and provides insights into future directions for ethnomathematics in education. The growing need for culturally responsive and inclusive education requires a place for ethnomathematics in curricula. Developed from the foundation of Vygotsky's (1978) theory of constructivist learning, Ladson-Billings' (1995) culturally responsive pedagogy, and Lave and Wenger's (1991) situated learning theory, this research investigates the nexus of ethnomathematics and progressive education models. This research uses a qualitative research approach involving a systematic literature review according to PRISMA guidelines, document analysis, and comparative case studies. The literature review establishes the main advantages and difficulties of ethnomathematics integration, analyzing approaches to embedding ethnomathematical principles into curriculum development. This study proposed a universal framework for Ethnomathematics integration into the curriculum. Through this thorough approach, the research highlights the potential of ethnomathematics to revolutionize mathematics education as a more inclusive, relevant, and socially responsive subject.